Lithobezoar: a case report - Chowksey, Sanjeev; Deshmukh, Satish; Kalbande, Samrudhi (International Surgery Journal, 2019)
We present a unique case of a colonic lithobezoar in a relatively healthy, young male with no history of psychological or psychiatric disorders. Furthermore, unlike previously reported cases, this patient had no history of gastric surgery. The mode of presentation and the rariety of disease pose difficulties in diagnosis of lithobezoar. The different modalities of treatment, both surgical and nonsurgical, were thought of and discussed. The diagnosis of a lithobezoar in a healthy patient requires a high index of suspicion, as it presents with nonspecific symptoms. The standard treatment for bezoars is discussed but lithobezoar needs special mention due to its rariety and no specific surgery guidelines.